2018
DOI: 10.12659/msm.910325
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Deferoxamine on Leukemia In Vitro and Its Related Mechanism

Abstract: BackgroundThis study aimed to investigate the effect of deferoxamine (DFO) on leukemia in vitro, and to explore the underlying molecular mechanism.Material/MethodsK562 leukemia cells were treated with various concentrations of DFO (10, 50, and 100 μmol/l) with or without 10 μmol/l ferric chloride for 12 h. Then, total cellular iron was detected. CCK-8 kit and flow cytometry were used for cell viability and apoptosis detection. In addition, expression of apoptosis-related genes was determined by Western blottin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Many previous studies reported that iron deprivation has a great potential in cancer treatment in in vitro conditions, 6,11‐15 and DFO has been most extensively investigated as the efficient iron chelator because of its excellent iron‐selectivity and safety 7,10 . However, only a few studies have demonstrated its in vivo therapeutic efficiency probably due to its poor biodistribution.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many previous studies reported that iron deprivation has a great potential in cancer treatment in in vitro conditions, 6,11‐15 and DFO has been most extensively investigated as the efficient iron chelator because of its excellent iron‐selectivity and safety 7,10 . However, only a few studies have demonstrated its in vivo therapeutic efficiency probably due to its poor biodistribution.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the hexadentate ligand prevents Fe(III) from producing hydroxy radicals via Fenton reaction, 7,9,10 which may contribute to avoidance of untoward toxicity. Previous studies have demonstrated that numerous cancer cell lines are sensitive to iron depletion by DFO 6,11‐15 . In addition, several clinical studies have shown that DFO exhibits antitumor activity in patients with neuroblastoma, leukemia, and hepatocellular carcinoma 16‐18 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies have confirmed that diminishing iron content inhibits tumor cell proliferation and induces apoptosis (54,55). Out of the various iron-chelators available, DFO is the most widely used iron-chelator and has shown to display these anti-tumor effects (56,57).…”
Section: Screening Of Therapeutic Drug Moleculesmentioning
confidence: 99%